An electronic nose to evaluate fungal contamination - GOBBI, EMANUELA; LOCCI, ROMANO (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2006)
Following an introduction on the characteristics and potentialities of electronic noses, results obtained using an EOS853 instrument on maize samples inoculated with Fusarium verticillioides strains are illustrated. The technique appears suitable for the rapid separation of samples colonized by either fumonisin B1 producing or non producing cultures.